PENGARUH PELATIHAN, KOMPETENSI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN PENDIDIKAN SEBAGAI PEMODERATOR PADA BALAI PENDIDIKAN DAN PELATIHAN APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN - Wahyu Yulianto (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
The study purpose is to analyse the impact of training, competence, motivation and leadership towards performance either directly or through job satisfaction as a mediator variable. As many as 55 staff are considered as respondents in this research, and census method is used as the sampling method. Primary data in this study were collected through questionnaires and analyzed using Likert Scale. Secondary data are obtained from the organization structure Sukamandi Apparatus Training Centre (BDA), performance appraisal, staff attendance, information system and personnel management. Structural Equation Modeling Analisis of Moment Structures (SEM-AMOS) is used to process and analyze data. This study shows staff with high education, competence and leadership have a significant effect on performance, While the job satisfaction is significant in mediating the influence of training, competence and leadership on performance. Next on the employee with low education, training, competence, motivation and leadership have a significant influence on performance, while job satisfaction is significant in mediating the effect of competence and leadership on staff performance. Keywords: training, competence, motivation, leadership, job satisfaction, performance